Intrusive Seismic Swarms as Possible Precursors of Destructive Earthquakes on Mt. Etna’s Eastern Flank - Salvatore Gambino; Giovanni Distefano (International Journal of Geophysics)
The Timpe Fault System (TFS) represents the source of shallow earthquakes that strike numerous towns and villages on Mt. Etna’s eastern flank. In the last 40 years, three destructive seismic events reached I0=VIII EMS (heavily damaging) in 1984 (October 25), 2002 (October 29), and 2018 (December 26). These events followed a few days after the occurrence of strong seismic swarms and the sudden acceleration of the eastern flank seaward. The damaging seismic events in 2002 and 2018 were associated with dike intrusions and eruptions of the volcano; however, no eruptive activity was observed at the time of the 1984 earthquakes. In this study, we investigate seismic parameters for the 1984 sequence, in order to interpret the seismicity in terms of volcanic activity. Parameters such as localization, cumulative seismic moment, and hourly occurrence frequency of the 1984 seismic swarm have been analysed and shown to have typical values of Mt. Etna’s intrusive seismic swarms. This suggests that the 1984 episode may have been an aborted intrusive magma episode that triggered similar processes (long and powerful intrusions with acceleration of the eastern flank movement and destructive earthquakes), as in 2002 and 2018. These three episodes suggest that an evaluation of some seismic parameters during future intrusive swarms may furnish indications of a possible reactivation of the TFS.